2016
DOI: 10.1007/s12665-015-5064-5
|View full text |Cite
|
Sign up to set email alerts
|

Permeability variations within mining-induced fractured rock mass and its influence on groundwater inrush

Abstract: This paper is concerned with the evaluation of permeability of fractured rock mass due to the cover stress re-establishment, which is a major factor in controlling water and gas flow rate induced by mining operations in fractured rock. The case study considered in this paper is based on the results of observations of groundwater inrush and a decrease in water inflow from the fractured roof strata due to mining advancing in the Taiping Coalmine, Shandong Province, China. A conceptual model of an effective porou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…In-situ monitoring of water inflow and pressure variations with time and mining distance in the water inrush process (Wang et al 2016) In the same coalfield, a borehole TV viewer system was used to monitor the fracture closure after the coal excavation 15 years ago. The results shown in Fig.…”
Section: Figmentioning
confidence: 99%
“…In-situ monitoring of water inflow and pressure variations with time and mining distance in the water inrush process (Wang et al 2016) In the same coalfield, a borehole TV viewer system was used to monitor the fracture closure after the coal excavation 15 years ago. The results shown in Fig.…”
Section: Figmentioning
confidence: 99%
“…Nourani et al and Poulsen et al revealed that the overlying strata permeability was directly related to porosity and proposed a method for rock permeability evaluation based on the porosity parameters [18,19]. Wang et al and Karacan et al reported that rocks in the goaf gradually supported the overlying roof with the panel advance, while the stress redistribution in the overlying strata caused the overlying rock permeability decline [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Zou et al [40] examined the fracture surface of natural granite rock using laser and established the fracture model of roughness characterization and fluid flowing simulation. Wang et al [41] acquired the roughness of the joint surface in the rocks using 3D-laser-scanning-based rock surface meter.…”
Section: Introductionmentioning
confidence: 99%